(untitled) (SAARC Journal of Agriculture, 2018)
A study was conducted in Horticulture farm of Agriculture and Forestry University, Rampur, Chitwan, Nepal, during November 2015 to February 2016 by using three commercial radish varieties (All Season White, Mino Early Long White and Pyuthane Red) and five nutrient sources combination of organic manure (Poultry and Farm yard manure) and recommended dose of inorganic fertilizer (100:80:40 NPK kg ha-1) replicated three times in a factorial RCBD design. Most of the plant growth and yield parameters were found superior in treatments consisting poultry manure (PM) alone and in combinations with inorganic fertilizer. Treatment consisting farm yard manure (FYM) was found inferior in most of the cases. At the time of harvest, significantly higher plant height (37.5 cm), number of leaves per plant (24.77), root diameter (39.01 mm), average leaf length (35.03 cm), average leaf width (12.86 cm) was observed in treatment consisting PM (50%) and RDF (50%). Similarly, root yield (73.98 t ha-1) and shoot yield (62.52 t ha-1) was also found higher in the same treatment. Among the three commercial radish varieties, Mino Early Long White was found superior in most of the growth and yield parameters viz., number of leaves per plant, biological yield, root yield, root length, root diameter, marketable root, smooth root and excellent fleshed root percentage. SAARC J. Agri., 16(1): 61-69 (2018)